2018
DOI: 10.1161/atvbaha.118.311289
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of FAM3D (Family With Sequence Similarity 3, Member D), A Novel Chemokine, Attenuates Neutrophil Recruitment and Ameliorates Abdominal Aortic Aneurysm Development

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…FAM3D is a gut-secreted protein reported to be regulated by nutritional status with unknown function 13 . FAM3D (Fam3D) was subsequently identified as a host-derived endogenous chemotactic agonist for the G-protein coupled receptors, namely formyl peptide receptor (FPR)1 and FPR2 (mouse Fpr1 and Fpr2) 14 , suggesting its proinflammatory properties 15 . However, the role of FAM3D (Fam3D), constitutively and abundantly expressed in the gastrointestinal tract, in the homeostasis and pathological conditions in the colon remains unclear.…”
mentioning
confidence: 99%
“…FAM3D is a gut-secreted protein reported to be regulated by nutritional status with unknown function 13 . FAM3D (Fam3D) was subsequently identified as a host-derived endogenous chemotactic agonist for the G-protein coupled receptors, namely formyl peptide receptor (FPR)1 and FPR2 (mouse Fpr1 and Fpr2) 14 , suggesting its proinflammatory properties 15 . However, the role of FAM3D (Fam3D), constitutively and abundantly expressed in the gastrointestinal tract, in the homeostasis and pathological conditions in the colon remains unclear.…”
mentioning
confidence: 99%
“…Patients with AAA demonstrate increased blood neutrophil counts and neutrophil activation marker NGAL (neutrophil gelatinase‐associated lipocalin) . Targeting neutrophils with antibodies or blocking chemokine expression necessary for neutrophil recruitment ameliorates experimental AAA formation . Here, we revealed a role of IgE in regulating neutrophil expression of CXC chemokines CXCL5 and MIP‐2α that have been shown essential to neutrophil chemoattraction .…”
Section: Discussionmentioning
confidence: 88%
“…45 Targeting neutrophils with antibodies or blocking chemokine expression necessary for neutrophil recruitment ameliorates experimental AAA formation. 7,8,14 Here, we revealed a role of IgE in regulating neutrophil expression of CXC chemokines CXCL5 and MIP-2α that have been shown essential to neutrophil chemoattraction. [46][47][48][49] That is probably why we detected many fewer neutrophils in AAA lesions from the Apoe −/− Ige −/− mice than those in Apoe −/− mice ( Figure 4B,D).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…FAM3D has demonstrated a high affinity for both FPR1 and FPR2 and has been implicated in playing an important role in both inflammation and GI homeostasis via FPR activation [75]. Additional studies have found that FAM3D may also be involved in the beneficial role of glucagon secretion in Type 2 diabetes, as well as the detrimental development of abdominal aortic aneurysms [76,77].…”
Section: Host-derived Fpr Ligandsmentioning
confidence: 99%